Trends, district-level variations, and socioeconomic disparities in cesarean section delivery in Bangladesh - Md Nuruzzaman Khan; Md Badsha Alam; Shimlin Jahan Khanam; M. Mofizul Islam; Md Arif Billah (PLoS ONE, 2025)
Background Cesarean section (CS) delivery rates have risen dramatically worldwide, with most countries exceeding the World Health Organization’s (WHO) recommended rate of 10–15%. However, disparities exist, with evidence suggesting that socioeconomic disadvantage and geographic location significantly influence CS rates. Despite this, comprehensive estimates, particularly in Bangladesh, remain limited. This study aims to examine trends, district-level variations, and socioeconomic disparities in CS rates in Bangladesh. Methods Data from seven rounds of the Bangladesh Demographic and Health Surveys, conducted between 1999/2000 and 2022, were analyzed. The outcome variable was CS delivery, categorized by mode of delivery and place of delivery. Explanatory variables included districts, wealth quintiles, and socio-demographic characteristics. Descriptive statistics were used to illustrate trends and variations in CS delivery over time in Bangladesh. Multilevel mixed-effects binary logistic regressions were employed to identify the factors associated with CS delivery. Results Between 1999/2000 and 2022, hospital births in Bangladesh increased by 55%, largely driven by a significant rise in CS deliveries, from 32% to 69%. Around 85% of the total CS deliveries occurred in the private healthcare facilities in 2022, a marked increase from 41.5% in 1999/2000. In contrast, CS delivery rates in government healthcare facilities fell from 53% to 13.6% during the same period. Mothers in border and hilly districts, as well as those in the poorest wealth quintile, reported lower rates of CS delivery compared to their counterparts. Conclusion The uneven distribution of CS delivery across districts and socioeconomic groups highlights the need for a more tailored approach to childbirth. While government efforts to reduce unnecessary CS use have been insufficient, this study suggests that a one-size-fits-all strategy may exacerbate disparities. Instead, the focus should shift from increasing access to ensuring justified and appropriate use of CS, with public healthcare facilities playing a crucial role in providing safe alternatives.